The Pedagogy of Hidden Curriculum in Pesantren: Institutional Culture and Character Internalization in Basic Advanced Course (KMD) Programs - Faridj Febrian Bustami; Sani Abdu Hamidullah; Saiful Anwar; Saepul Anwar; Syarifah (CV Putra Publisher, 2026)
This study explores the pedagogy of the hidden curriculum in Basic Advanced Course (Kursus Mahir Dasar/KMD) programs and its role in character internalization at Pondok Modern Darussalam Gontor. The research aims to analyze how institutional culture, social interaction, and value habituation function as pedagogical mechanisms in shaping students’ character within pesantren education. This study employed a qualitative case study approach. Data were collected through participatory observation, semi-structured interviews, and documentation involving KMD participants, supervising ustadz, and organizational mentors. Data analysis was conducted thematically through data condensation, interpretation, and conclusion drawing. The findings reveal that the hidden curriculum operates intensively through the pesantren’s twenty-four-hour institutional culture, exemplary role modeling, leadership practices, and experiential learning activities. Character values such as discipline, responsibility, independence, cooperation, leadership, and self-confidence were internalized through repetitive habituation and direct social engagement rather than through formal instruction alone. The study further demonstrates that KMD activities function as a strategic experiential learning arena where organizational responsibilities and communal interactions strengthen students’ moral and social development. The novelty of this study lies in positioning the hidden curriculum as an intentional pedagogical ecosystem embedded within leadership-based experiential education in pesantren. This research contributes theoretically to hidden curriculum discourse and practically to the development of holistic character education models in Islamic educational institutions.